Dietary potato intake and risks of type 2 diabetes and gestational diabetes mellitus. Issue 6 (June 2021) - Guo, Fang; Zhang, Qiang; Jiang, Hong; He, Yuan; Li, Ming; Ran, Jinjun; Lin, Jing; Tian, Linwei; Ma, Le
Summary: Background & aims: Evidence regarding associations between potato consumption and type 2 diabetes (T2D) and gestational diabetes mellitus (GDM) risks is accumulating. This study aims to synthesize the evidence by conducting a meta-analysis of available studies. Methods: PubMed, Web of Science, EMBASE and Cochrane Library were searched (up to August 2020) to retrieve all eligible studies on the associations of interest. The risk estimates with 95% confidence intervals (CIs) were summarized using random- or fixed-effects model based on heterogeneity. Meta-analyses were performed for East and West regions separately. Dose–response relationship was assessed using data from all intake categories in each study. Results: A total of 19 studies (13 for T2D; 6 for GDM) were identified, including 21, 357 T2D cases among 323, 475 participants and 1516 GDM cases among 29, 288 pregnancies. Meta-analysis detected a significantly positive association with T2D risk for total potato (RR: 1.19 [1.06, 1.34]), baked/boiled/mashed potato (RR: 1.08 [1.00, 1.16]), and French fries/fried potato (RR: 1.33 [1.03, 1.70]) intakes among Western populations. Dose–response meta-analysis demonstrated a significantly increased T2D risk by 10% (95% CI: 1.07, 1.14; P for trend<0.001), 2% (95% CI: 1.00, 1.04; P for trend = 0.02) and 34% (95% CI: 1.24, 1.46; P for trend<0.001) for each 80 g/day (serving) increment in total potato, unfried potato, and fried potato intakes, respectively. As for GDM, summarized estimates also suggested a higher though non-significant GDM risk for total potato (RR: 1.19 [0.89, 1.58]), and French fries/fried potato (RR: 1.03 [0.97, 1.09]) intakes in Western countries. In the dose–response meta-analysis, a significantly increased GDM risk was revealed for each daily serving (80 g) intakes of total potato (RR: 1.22; 95% CI: 1.06, 1.42; P for trend = 0.007) and unfried potato (RR: 1.26; 95% CI: 1.07, 1.48; P for trend = 0.006). Conclusions: This study suggests that higher potato intake is associated with higher T2D risk among Western populations. The positive relationship presents a significant dose–response manner. Wisely controlled potato consumption may confer potential glucometabolic benefits.